Answer:
[tex]\huge\boxed{y=-x-1}[/tex]
Step-by-step explanation:
The slope-intercept form of an equation of a line:
[tex]y=mx+b[/tex]
[tex]m[/tex] - slope
[tex]b[/tex] - y-intercept
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
[tex](x_1;\ y_1)[/tex] - point on a line
========================================
We have
[tex]m=-1;\ (-4;\ 3)\to x_1=-4;\ y_1=3[/tex]
substitute
[tex]y-3=-1(x-(-4))\\\\y-3=-(x+4)\\\\y-3=-x-4\qquad|\text{add 3 to both sides}\\\\y-3+3=-x-4+3\\\\y=-x-1[/tex]